Assessment of real-time data transmission via ad-hoc communication networks in the North Atlantic Oceanic airspace - Hillebrecht, Alexander; Marks, Tobias; Gollnick, Volker (Curran, 2022)
Data link based real-time data transmission for air traffic services and aeronautical operational control provides for safe, efficient and timely exchange of information between aircraft and ground entities within the current air transportation system. This enables procedures and process optimization for air traffic service and airline operational control. Currently, the air transport system relies on direct line-of-sight data link in continental airspace and communication via satellite or high frequency data link in oceanic, remote or polar airspace. Future communication technology intends to additionally allow for indirect air-to-ground communication via aeronautical ad-hoc networks using aircraft as network nodes. This approach bears a high potential to increase airspace capacity and efficiency for congested airspaces with little ground infrastructure as it is the case e.g. for the North Atlantic oceanic airspace. While the assessment of operational benefits for conventional line-of-sight or satellite-based data link technologies can be based on the experience made with existing technologies, the assessment of aeronautical ad-hoc networks needs careful consideration of the particular air traffic situation as well as of the specific aeronautical communication demand. In our work we present a method to combine air traffic and connectivity simulations with an aeronautical data traffic demand model for the North Atlantic oceanic airspace. As a result, the coverage of aeronautical data traffic demand by an aeronautical ad-hoc network enabled by the new technology, will be estimated for various scenarios for the North Atlantic oceanic airspace. Dependencies on the equipage fraction and on the air-to-air radio range will be analyzed. Also, expected application data rates at aircraft exchanging the data communication of the airborne network with ground entities, will be assessed on a simplified basis. The results are suited to serve as a technical guidance for further scaling and definition of the underlying ...